Collins KS3 science workbook 1 - Walsh, Edmund (Peak Publishing; Pakistan, 2008)
* Written especially for lower ability students * For every lesson spread in the Pupil Book 2 there is a corresponding Workbook page of write-in exercises, helping with Progression * Workbook 2 covers levels 2 to 3 * Allows lower ability students to access the new Program of Study and Framework * Workbook 2 gives practice for those working at levels 2 to 4, with one write-in page of questions and exercises to correspond with every lesson spread in Pupil Book 2 * These full color workbooks are packed with stimulating and engaging exercises that will encourage progression, as well as access to How Science Works